Implications of duplicated cis-regulatory elements in the evolution of metazoans: the DDI model or how simplicity begets novelty. - Jiménez-Delgado, Senda; Pascual-Anaya, Juan; Garcia-Fernàndez, Jordi (Oxford Academic, 2009)
The discovery that most regulatory genes were conserved among animals from distant phyla challenged the ideas that gene duplication and divergence of homologous coding sequences were the basis for major morphological changes in metazoan evolution. In recent years, however, the interest for the roles, conservation and changes of non-coding sequences grew-up in parallel with genome sequencing projects. Presently, many independent studies are highlighting the importance that subtle changes in cis -regulatory regions had in the evolution of morphology trough the Animal Kingdom. Here we will show and discuss some of these studies, and underscore the future of cis -Evo-Devo research. Nevertheless, we would also explore how gene duplication, which includes duplication of regulatory regions, may have been critical for spatial or temporal co-option of new regulatory networks, causing the deployment of new transcriptome scenarios, and how these induced morphological changes were critical for the evolution of new forms. Forty years after Susumu Ohno famous sentence ‘natural selection merely modifies, while redundancy creates’, we suggest the alternative: ‘natural selection modifies, while redundancy of cis -regulatory elements innovates’, and propose the Duplication ^Degeneration ^Innovation model to explain the increased evolvability of duplicated cis -regulatory regions. Paradoxically, making regulation simpler by subfunctionalization paved the path for future complexity or, in other words, ‘to make it simple to make it complex’.
https://v2.sherpa.ac.uk/id/publication/16032?template=romeo
Keywords: Genómica; Genética evolutiva; Animales; Evo-Devo; Metazoos; Evolución; Modelo DDI; Duplicación génica; Regulación en cis